The Antidepressant Agomelatine Improves Memory Deterioration and Upregulates CREB and BDNF Gene Expression Levels in Unpredictable Chronic Mild Stress (UCMS)-Exposed Mice - Esen Gumuslu (Drug Target Insights, 2014)
Agomelatine, a novel antidepressant with established clinical efficacy, acts as an agonist of melatonergic MT 1 and MT 2 receptors and as an antagonist of 5-HT 2C receptors. The present study was undertaken to investigate whether chronic treatment with agomelatine would block unpredictable chronic mild stress (UCMS)-induced cognitive deterioration in mice in passive avoidance (PA), modified elevated plus maze (mEPM), novel object recognition (NOR), and Morris water maze (MWM) tests. Moreover, the effects of stress and agomelatine on brain-derived neurotrophic factor (BDNF) and cyclic adenosine monophosphate (cAMP) response element binding protein (CREB) messenger ribonucleic acid (mRNA) levels in the hippocampus was also determined using quantitative real-time polymerase chain reaction (RT-PCR). Male inbred BALB/c mice were treated with agomelatine (10 mg/kg, i.p.), melatonin (10 mg/kg), or vehicle daily for five weeks. The results of this study revealed that UCMS-exposed animals exhibited memory deterioration in the PA, mEPM, NOR, and MWM tests. The chronic administration of melatonin had a positive effect in the PA and +mEPM tests, whereas agomelatine had a partial effect. Both agomelatine and melatonin blocked stress-induced impairment in visual memory in the NOR test and reversed spatial learning and memory impairment in the stressed group in the MWM test. Quantitative RT-PCR revealed that CREB and BDNF gene expression levels were downregulated in UCMS-exposed mice, and these alterations were reversed by chronic agomelatine or melatonin treatment. Thus, agomelatine plays an important role in blocking stress-induced hippocampal memory deterioration and activates molecular mechanisms of memory storage in response to a learning experience.